2009
DOI: 10.1016/j.ijimpeng.2008.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Ignition of a confined high explosive under low velocity impact

Abstract: In the framework of low velocity impact studies, dedicated to safety analyses of plastic bonded explosives (PBX), we propose a new numerical tool, designed for restituting the ignition of a HMX (high melting point explosive) based composition. Major results are the use of a concrete-like constitutive law for the PBX and an efficient implementation of an ignition criterion. We also put forward two variants of classical Steven tests, which enable us to visualize either a dot ignition or an unusual ring-shaped ig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
46
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 74 publications
(46 citation statements)
references
References 16 publications
0
46
0
Order By: Relevance
“…Lastly, the end of the signal indicated gauge failure with the pyrotechnic reaction of the high explosive. Gruau et al [7] performed some numerical simulations of these experiments. To this end, they developed a numerical tool based on the ABAQUS/Explicit finite element code and a concretelike constitutive property for the high explosive [8][9].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Lastly, the end of the signal indicated gauge failure with the pyrotechnic reaction of the high explosive. Gruau et al [7] performed some numerical simulations of these experiments. To this end, they developed a numerical tool based on the ABAQUS/Explicit finite element code and a concretelike constitutive property for the high explosive [8][9].…”
Section: Introductionmentioning
confidence: 99%
“…To this end, they developed a numerical tool based on the ABAQUS/Explicit finite element code and a concretelike constitutive property for the high explosive [8][9]. Gruau and Picart [10] determined the material parameters. The simulation of the configuration reported in Figure 1 exhibited a mean plastic strain rate of 10 5 s -1 , a maximal pressure close to 500 MPa and a finite strain approaching 0.5.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it was shown that some explosive compositions reacted violently when submitted to a low velocity impact (the pressure is far from the shock to detonation transition threshold) [1]. The mechanical behavior of the explosive is one of the keys needed to predict such an event [2][3].…”
Section: Introductionmentioning
confidence: 99%
“…Experimental impact tests and numerical studies [3] have clarified the loading conditions during low velocity impact. The pressure can reach 300 to 500 MPa when a strain rate equal to 10 4 s -1 is expected, as well as finite strains approaching 1.…”
Section: Introductionmentioning
confidence: 99%